2019
DOI: 10.12659/msm.913358
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Integrated Care in Management of Advanced Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a common disease that occurs all over the world. Models of care, initially accessed from the clinical point of view, must also be evaluated in terms of their economic effectiveness, as health care systems are limited. The Integrated Care Model (ICM) is a procedure dedicated to patients suffering from advanced COPD that offers home-oriented support from a multidisciplinary team. The main aim of the present study was to evaluate the cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…10,96 Moreover, CEAs of integrated approaches in different disease areas often tend to have positive results, such as improved cost-effectiveness of the integrated care management versus the standard care of advanced chronic obstructive pulmonary disease. 97 This integrated approach of PN deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…10,96 Moreover, CEAs of integrated approaches in different disease areas often tend to have positive results, such as improved cost-effectiveness of the integrated care management versus the standard care of advanced chronic obstructive pulmonary disease. 97 This integrated approach of PN deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[17][18][19] The recent evidence of the integrated care management approach further supports the benefit of a multidisciplinary team to reduce ED visits and hospital admissions. 20 The streamlined unified meaningfully managed interdisciplinary team (SUMMIT) trial protocol shows further interest in the multidisciplinary approach to care in an urban homelessness setting; results of the trial are not yet available. 21 In contrast, the current study demonstrated reduced COPD hospitalization rates in a primary care rural clinic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Human resource cost was also the highest cost in a team-based chronic care model [36]. In a study in Poland, the addition of integrated home-orientated services that included education and family support for patients with advanced chronic obstructive pulmonary disease (COPD) reduced the overall cost of care from the health system perspective [38]. The main reasons for cost reduction were reduced hospitalizations and disease exacerbations [38].…”
Section: Plos Onementioning
confidence: 99%
“…In a study in Poland, the addition of integrated home-orientated services that included education and family support for patients with advanced chronic obstructive pulmonary disease (COPD) reduced the overall cost of care from the health system perspective [38]. The main reasons for cost reduction were reduced hospitalizations and disease exacerbations [38]. However, in other studies, the chronic care model reduced costs related to unplanned hospitalization, but increased costs for out-patient consultations and medication [39,40].…”
Section: Plos Onementioning
confidence: 99%